PERAN LURAH DALAM PEMBERDAYAAN MASYARAKAT DI KELURAHAN BANGKO KIRI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR TAHUN 2017 - Adi Pradinata Tarigan; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Referring to the laws and regulations governing the Regional Government, namely Law Number 23 of 2014, it is stated that the village is formed by the regional government and appoints a village chief called the headman as the sub-district apparatus and is responsible to the camat. This study aims to look at the extent of the role of the village of Bangko kiri as a counselor or facilitator of community empowerment in terms of human development, business development, institutional development, and environmental development. Empowerment in human development in the village of Bangko kiri is done by forming farmer groups that aim to help farmers in agricultural business both in the form of seeds and fungicides and agricultural counseling, so that it is expected to be able to improve the quality of the community. Business development in the village of Bangko left is carried out by providing loan capital assistance with relatively low interest that is expected to be able to develop community businesses. Institution building is done by providing guidance, coaching, and / or directing to existing institutions such as LPM, PKK, Youth and so forth. In the case of environmental development in the village of left Bangko is carried out by mutual cooperation and religious guidance. The results of this study indicate that the Bangko kiri headman village has not actively and optimally played a role in empowerment. Empowerment in Bangko kiri village is not yet succes. This is evidenced by the low level of community participation and empowerment programs that have not been able to touch the poverty problems experienced by the community. In 2017, there were 111 families of poor people in Bangko Kiri village out of 531 families in that village. The non-optimal empowerment program can also be seen from the number of farm families as many as 470 families, but those who join farmer groups are 250 families. Keywords: Role, Empowerment, Village, Facilitator